Functional and phenotypic evaluation of eosinophils from patients with the acute form of paracoccidioidomycosis. - Fernanda Gambogi Braga; Luciana Pereira Ruas; Ricardo Mendes Pereira; Xinaida Taligare Lima; Edson Antunes; Ronei Luciano Mamoni; Maria Heloisa Souza Lima Blotta (Public Library of Science (PLoS), 2017)
Eosinophilia is a typical finding of the acute/juvenile form of paracoccidioidomycosis (PCM), a systemic mycosis endemic in Latin America. This clinical form is characterized by depressed cellular immune response and production of Th2 cytokines. Moreover, it has been shown that the increased number of eosinophils in peripheral blood of patients returns to normal values after antifungal treatment. However, the role of eosinophils in PCM has never been evaluated. This study aimed to assess the phenotypic and functional characteristics of eosinophils in PCM.In 15 patients with the acute form of the disease, we detected expression of MBP, CCL5 (RANTES) and CCL11 (eotaxin) in biopsies of lymph nodes and liver. In addition, there were higher levels of chemokines and granule proteins in the peripheral blood of patients compared to controls. Isolation of eosinophils from blood revealed a higher frequency of CD69+ and TLR2+ eosinophils in patients compared to controls, and a lower population of CD80+ cells. We also evaluated the fungicidal capacity of eosinophils in vitro. Our results revealed that eosinophils from PCM patients and controls exhibit similar ability to kill P. brasiliensis yeast cells, although eosinophils of patients were less responsive to IL-5 stimulation than controls.In conclusion, we suggest that eosinophils might play a role in the host response to fungi and in the pathophysiology of PCM by inducing an intense and systemic inflammatory response in the initial phase of the infection.